Effects of Peroxisome Proliferator-Activated Receptor Ligands on the Hypothalamic-Pituitary-Gonadal Axis of the Male Goldfish - Cameron, Colin (University of Ottawa (Canada), 2011)
Fibrate pharmaceuticals are peroxisome proliferator-activated receptor alpha (PPARalpha) ligands that are detected in sewage treatment plant effluents, surface water and groundwater. In a previous study, male goldfish ( Carassius auratus) exposed to the fibrate gemfibrozil (GEM) in the water exhibited decreased plasma testosterone concentrations. The following studies investigate the effects of GEM and other PPAR ligands on components of the hypothalamic-pituitary-gonadal axis of the male goldfish; the pituitary and testes. In vitro cultures of dispersed goldfish pituitary cells and testis fragments were employed to study these two tissues in isolation. The secretion of neither luteinizing hormone nor growth hormone from pituitary cells was affected in a manner that could explain decreases in circulating testosterone. Testosterone synthesis in testis fragments stimulated with human chorionic gonadotropin (hCG) was suppressed following treatment with GEM. This inhibition appeared to be the result of impaired mitochondrial cholesterol transport. However, changes in the expression of two proteins important for mitochondrial cholesterol transport, steroidogenic acute regulatory protein and peripheral benzodiazepine receptor, were not affected by GEM treatment. Investigations on the involvement of extracellular-regulated signal kinase 1/2 (ERK 1/2) in the steroidogenic pathway revealed that phosphorylated ERK 1/2 (P-ERK 1/2) is required for hCG-stimulated testosterone synthesis and that GEM treatment decreased levels of P-ERK 1/2 in the mitochondria of this tissue. The main conclusions from these studies include the following: (1) The effect of waterborne GEM on the HPG axis of the goldfish is a direct effect on the testis, (2) GEM impairs mitochondrial cholesterol transport in the goldfish testis, (3) Phospho-ERK 1/2 is required for hCG-stimulated steroidogenesis in the goldfish testis, and (4) the proposed mechanism by which GEM impairs mitochondrial cholesterol transport is through a reduction in mitochondrial phospho-ERK 1/2.
Keywords: Biology, Endocrinology.